National integrated mitigation planning in agriculture: a review paper - Wilkes, Andreas; Tennigkeit, Timm; Solymosi K (Food and Agriculture Organization of the United Nations, 2013)
Purpose and scope of the review: This review of national greenhouse gas (GHG) mitigation planning in the agriculture sector has two objectives: (i) to provide national policy makers and others in the agriculture sector with an overview of national mitigation planning processes and aid then in identifying the relevance of these processes for promoting agricultural development; (ii) to provide policy makers and advisors involved in low-emission development planning processes with an overview of mitigation planning in the agriculture sector and in particular to highlight the relevance of agriculture to national mitigation plans and actions. The review provides an overview of agreements under the United Nations Framework Convention on Climate Change (UNFCCC) on GHG mitigation in developing countries (Section 1.2). It distinguishes between low-emission development strategies (LEDS), which aim to guide a transition to a low-emission development pathway, and Nationally Appropriate Mitigation Actions (NAMAs), which are mitigation policies and measures undertaken in line with national development strategies. Chapter 2 reviews 32 LEDS from 18 developing countries. It provides summary analysis of the planning processes, the types of plans that have been produced and the contents of these plans. Chapter 2 also analyses the alignment of these LEDS with other policy goals and enabling conditions for planning, and summarizes lessons that have been gained from experience. Chapter 3 reviews 62 NAMAs in the agriculture sectors of 30 countries. It describes the status of development of the NAMAs, the agricultural activities proposed and the alignment of the NAMAs with other policies and policy goals. Chapter 3 also identifies key elements that support the development of the conception, design and implementation of NAMAs. Chapter 4 summarizes the status of and trends in national agricultural mitigation planning, the barriers and risks involved, and the opportunities and potentials for agricultural NAMAs. It also suggests an approach to NAMA development in the agriculture sector based on 12 basic building blocks.